Correction: Evaluation of flood metrics across the Mississippi-Atchafalaya River Basin and their relation to flood damages. - Keith E Schilling; Elliot S Anderson; Jerry Mount; Kelly Suttles; Philip W Gassman; Natalja Čerkasova; Michael J White; Jeffrey G Arnold (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0307486.].